2000
DOI: 10.1126/science.287.5460.2020
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Antipsychotic-Induced Working Memory Deficits by Short-Term Dopamine D1 Receptor Stimulation

Abstract: Chronic blockade of dopamine D2 receptors, a common mechanism of action for antipsychotic drugs, down-regulates D1 receptors in the prefrontal cortex and, as shown here, produces severe impairments in working memory. These deficits were reversed in monkeys by short-term coadministration of a D1 agonist, ABT 431, and this improvement was sustained for more than a year after cessation of D1 treatment. These findings indicate that pharmacological modulation of the D1 signaling pathway can produce long-lasting cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
224
1
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 363 publications
(243 citation statements)
references
References 37 publications
16
224
1
2
Order By: Relevance
“…Moreover, the reduced performance was reversed by dopamine receptor agonists. A number of more recent studies have shown that mainly dopamine D 1 , but not D 2 , receptors are involved in the modulation of tasks relying on intact prefrontal cortical functioning Goldman-Rakic, 1991, 1994;Williams and Goldman-Rakic, 1995;Goldman-Rakic, 1996;Castner et al, 2000). Moreover, D 1 receptor density exceeds D 2 density by a factor of 10-20 in animal (Camps et al, 1990;Lidow et al, 1991) and human (De et al, 1988) cerebral cortex.…”
Section: The Effect Of Haloperidol On Neuropsychological Performancementioning
confidence: 99%
“…Moreover, the reduced performance was reversed by dopamine receptor agonists. A number of more recent studies have shown that mainly dopamine D 1 , but not D 2 , receptors are involved in the modulation of tasks relying on intact prefrontal cortical functioning Goldman-Rakic, 1991, 1994;Williams and Goldman-Rakic, 1995;Goldman-Rakic, 1996;Castner et al, 2000). Moreover, D 1 receptor density exceeds D 2 density by a factor of 10-20 in animal (Camps et al, 1990;Lidow et al, 1991) and human (De et al, 1988) cerebral cortex.…”
Section: The Effect Of Haloperidol On Neuropsychological Performancementioning
confidence: 99%
“…It is well known that dopamine (DA) neurotransmission plays a pivotal role in WM (Castner et al, 2000;McNab et al, 2009). Pharmacological studies on both animals (Vijayraghavan et al, 2007) and humans (Kimberg and D'Esposito, 2003) have indicated that dopamine (DA) in the brain modulates WM.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic exposure to the D 2 -like receptor antagonist haloperidol results in disrupted working memory (Castner et al, 2000). Acute challenge with various D 2 -like receptor antagonists has been reported to impair working memory and delayspecific PFC neuronal activity in some studies (Arnsten and Goldman-Rakic, 1998;Didriksen, 1995;Murphy et al, 1996), but not others (Aultman and Moghaddam, 2001;Bushnell and Levin, 1993;Sawaguchi and Goldman-Rakic, 1994;Verma and Moghaddam, 1996;Williams and GoldmanRakic, 1995).…”
Section: Introductionmentioning
confidence: 99%